DOI: 10.31274/etd-180810-4368
|View full text |Cite
|
Sign up to set email alerts
|

Overprivileged, self-absorbed, dumb jocks: exploration of stereotypes of student-athletes

Abstract: In this study, lists of traits typically associated with several groups of students were created using empirically supported methods. Specifically, these traits were grouped into a taxonomy based on the extent to which they were classified as being stereotypical for male student-athletes, female student-athletes, male non-athlete students, female non-athlete students, masculine individuals, feminine individuals, athletes, and non-athletes. The purpose behind this study was to create lists of stereotypes associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 90 publications
(124 reference statements)
2
12
0
Order By: Relevance
“…Extensive research has been conducted on the stereotypes and perceptions of studentathletes by non-athlete students (Anderson, 2015;Comeaux, 2018;Czopp, 2010), but little research has been conducted on student-athletes' perceptions of non-athletes. This study provides an understanding of how student-athletes perceive non-athletes, particularly as it relates to socialization outside of the athlete community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has been conducted on the stereotypes and perceptions of studentathletes by non-athlete students (Anderson, 2015;Comeaux, 2018;Czopp, 2010), but little research has been conducted on student-athletes' perceptions of non-athletes. This study provides an understanding of how student-athletes perceive non-athletes, particularly as it relates to socialization outside of the athlete community.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in college athletics has been shown to negatively impact student-athletes' social and personal development (Beamon, 2012;Singer, 2009) due to time constraints and the struggle with the dualrole of student and athlete (Clayton et al, 2015;Coakley, 2009;Coser, 1974;Lee, 2015;Rubin, 2016;Sack & Theil, 1985). In addition, male student-athletes commonly face strong stereotypes from peers, faculty, staff, and the general population based on their academic identity (Anderson, 2015;Edwards, 1984). Most notably, along racial lines, "dumb-jock" stereotypes can prove particularly detrimental to Black student-athletes in the classroom and among their non-athlete peers (Edwards, 1984;Rubin, 2016;Stone et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Non-Athlete Student, Female Non-Athlete Student)?" Due to different adjectives being assigned to each of the four categories, it is believed that participants will treat these groups differently (Anderson, 2015). Also, due to the disproportional nature of the numbers of men and women in most jobs (i.e., 98% of kindergarten teachers are women, while 97% of construction workers are men; Bureau of Labor Statistics, 2017), it is unlikely that an even distribution of each job title will occur in the present study.…”
Section: Hypothesis 1: Non-random Assignment To Categoriesmentioning
confidence: 92%
“…It is important to note that one does not need to endorse a stereotype to be aware of it. For example, an individual may be a supporter of equal employment opportunities for women and men, but when presented with stimuli associated with kindergarten teachers and construction workers may still associate these careers with their stereotypical gender roles (Anderson, 2015). Further evidence of this concept can be seen in the fact that Devine (1989) found that participants with both high and low prejudice ratings endorsed similar stereotypes of specific ethnic groups.…”
Section: Definitions Of Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation